Purification and properties of serine hydroxymethyltransferase from Sulfolobus solfataricus. - Delle Fratte, S (1997)
Serine hydroxymethyltransferase (SHMT) catalyzes the reversible cleavage of serine to glycine with the transfer of the one-carbon group to tetrahydrofolate to form 5,10-methylenetetrahydrofolate. No SHMT has been purified from a nonmethanogenic Archaea strain, in part because this group of organisms uses modified folates as the one-carbon acceptor. These modified folates are not readily available for use in assays for SHMT activity. This report describes the purification and characterization of SHMT from the thermophilic organism Sulfolobus solfataricus. The exchange of the alpha-proton of glycine with solvent protons in the absence of the modified folate was used as the activity assay. The purified protein catalyzes the synthesis of serine from glycine and a synthetic derivative of a fragment of the natural modified folate found in S. solfataricus. Replacement of the modified folate with tetrahydrofolate did not support serine synthesis. In addition, this SHMT also catalyzed the cleavage of both allo-threonine and beta-phenylserine in the absence of the modified folate. The cleavage of these two amino acids in the absence of tetrahydrofolate is a property of other characterized SHMTs. The enzyme contains covalently bound pyridoxal phosphate. Sequences of three peptides showed significant similarity with those of peptides of SHMTs from two methanogens.